(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Carvacrol, a widely extracted monoterpenoid phenol from an abundant number of aromatic plant species including thyme and oregano. At present, carvacrol is being utilized in low concentrations as a preservative and food flavoring agent, in addition to serving as a fragrance element in cosmetic formulations. A great deal of study has been done in recent years as an effort to determine the biological effects of carvacrol for possible therapeutic application. Carvacrol has been identified to have a vast range of biological and pharmacological characteristics which include antidiabetic, antimicrobial, antiinflammatory, anti-obesity, antitumor, hepatoprotective, gastroprotective, and neuroprotective effects based on both in vitro and in vivo experiments. The main objective of this review is to assess current understanding of carvacrol’s pharmacological impacts as well as its biosynthesis and plant sources in order to potentially inform the future researchers. It can be postulated that upon extensive research, this noteworthy bioactive phytochemical can be a very promising source of next generation drug development. Bangladesh Pharmaceutical Journal 27(1): 116-125, 2024 (January)